2016
DOI: 10.1111/jgs.14205
|View full text |Cite
|
Sign up to set email alerts
|

The International Dementia Alliance Instrument for Feasible and Valid Staging of Individuals with Dementia by Informal Caregivers

Abstract: Results of this study indicate good feasibility and high validity of staging dementia by informal caregivers using the IDEAL-IC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…During expert meetings, standardized questionnaires were collected, and additional questions were formulated. Standard questionnaires to measure resilience and wellbeing included the topics perseverance time, 35 burden, 36 social support, 37 physical health, 38 mental health, 39 person with dementia, 40 , 41 and resilience. 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During expert meetings, standardized questionnaires were collected, and additional questions were formulated. Standard questionnaires to measure resilience and wellbeing included the topics perseverance time, 35 burden, 36 social support, 37 physical health, 38 mental health, 39 person with dementia, 40 , 41 and resilience. 42 , 43 …”
Section: Resultsmentioning
confidence: 99%
“…During expert meetings, standardized questionnaires were collected, and additional questions were formulated. Standard questionnaires to measure resilience and wellbeing included the topics perseverance time, 35 burden, 36 social support, 37 physical health, 38 mental health, 39 person with dementia, 40,41 and resilience. 42,43 In a third meeting with end-users adjusted concept screens of the application and dashboard for case managers were presented and their relevance and user friendliness were discussed.…”
Section: Ideatementioning
confidence: 99%
“…Following this, a paper was published on the inter-rater reliability of the schedule in Ireland (ICCs ranged between 0.77 and 1.0 for the individual dimensions), as well as its criterion validity whereby the 'cognitive functioning' and 'carer stress' (sub-)dimensions of the IDEAL schedule, as well as its total sum score, were correlated with the Clinical Dementia Rating (CDR) scale (ρ=0.82 for 'cognitive functioning'; ρ=0.77 for total sum score) and Zarit Burden interview respectively (ρ=0.56) as a measure of criterion validity [22]. A further study from the Netherlands reported on the development and validation of a version that is completed by informal caregivers, the IDEAL-IC, by correlating this new version with the original clinician-administered IDEAL schedule (r= 0.7) and the Clinical Dementia Rating sum of boxes (CDR-SB) (r=0.65) as a measure of construct validity [23]. In this latter study, correlation between the original IDEAL schedule and the CDR-SB was also very high (r=0.85) [23].…”
Section: Recent Work On the Ideal Schedulementioning
confidence: 99%
“…A further study from the Netherlands reported on the development and validation of a version that is completed by informal caregivers, the IDEAL-IC, by correlating this new version with the original clinician-administered IDEAL schedule (r= 0.7) and the Clinical Dementia Rating sum of boxes (CDR-SB) (r=0.65) as a measure of construct validity [23]. In this latter study, correlation between the original IDEAL schedule and the CDR-SB was also very high (r=0.85) [23].…”
Section: Recent Work On the Ideal Schedulementioning
confidence: 99%